Product Packaging and Sales, in Competition with Consumers’ Psychology of Choice - Morakinyo, A. D.; Alkali, V. C. (NIU Journal of Humanities; Vol 8 No 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023, 2023)
The appearance of consumer products creates a particular impression that compels a consumer to make his choice of a product leading to sales. Product design is an opportunity for differential advantage in the market place. From secondary sources, information were collected and analysed on the roles that product appearance plays on the mind of consumers before choice is made.  A number of companies successfully focus on product design appearance as a competitive tool, and several studies indicate the influence of good product design packaging on commercial success. This, the ceramist in product development must queue into for the patronage of his wares by the consumer as a direction for advancement. Consumer preferences and consumer buying behaviour are the major issues that should be taken into account when designing new wares apart from just self-expression. The study found out that in spite of new technologies and materials, consumer's choices and desires constitute the most important elements that drive the marketing process. Therefore, the ceramic designer must put the customer in the fore front not himself when it comes to product appearance. The designer must also look into brand personality, the five (5) bran personality dimensions, deliberate feedback etc. as added issues to the six roles of product packaging to compel the psychology of consumers’’ choice and sales. Thus, the postmodernist philosophy of self-projection in our productive endeavours at the expense of consumer choice must be discouraged at this stage of development of ceramic if wares will compel their commercial values and retain customers’ loyalty beyond the five life cycle of a product. Keywords: Appearance, choice, comparative advantage, consumer, product.